Human Ecology
XIV, 377 p. 23 illus.
Keywords: This comprehensive sourcebook on human ecology combines 25 source articles published in the journal Human Ecology, enhanced with new research updates and thematic commentary. Intended as a follow up to Case Studies in Human Ecology, this volume includes an entirely new group of articles, with the same accessible, comprehensive coverage that made Case Studies so popular. Human Ecology: Research and Practice covers four important areas: Philosophy, Theory and Methods; Changing Subsistence Practices; Agricultural Intensification and Population Dynamics; and, Common Property Resources and Conservation. As a group, these articles represent the major contributions to the study of Human Ecology since the publication of the previous volume. Each article includes a concise introduction by the Editor, giving necessary and thoughtful context. The volume covers an overview of human ecology as a field within environmental studies, new directions in contemporary research, new methods and techniques, and cultural landscapes. Anyone studying human ecology, environmental studies, landscape studies, or population dynamics, particularly key issues such as conservation and globalization will find this comprehensive reader a valuable resource.